Mitochondrial fragmentation in neuronal degeneration: Toward an understanding of HD striatal susceptibility - Cherubini, M; Ginés, S (Elsevier, 2016)
Huntington's disease (HD) is an autosomal-dominant progressive neurodegenerative disorder that primarily affects medium spiny neurons within the striatum. HD is caused by inheritance of an expanded CAG repeat in the HTT gene, resulting in a mutant huntingtin (mHtt) protein containing extra glutamine residues. Despite the advances in understanding the molecular mechanisms involved in HD the preferential vulnerability of the striatum remains an intriguing question. This review discusses current knowledge that links altered mitochondrial dynamics with striatal susceptibility in HD. We also highlight how the modulation of mitochondrial function may constitute an attractive therapeutic approach to reduce mHtt-induced toxicity and therefore prevent the selective striatal neurodegeneration.